Bait Al-Hikma and its Cultural Impact till the end of the first Abbasid era (218 AH | 833 AD( (Journal of the College of Basic Education, 2022)
The interest and care of the Abbasid caliphs, led by Abu Jaafar al-Mansur, Harun al-Rashid and al-Ma’mun, in the scientific and intellectual movement in Baghdad since its foundation, resulted in the establishment of (Bait Al-Hikma) (House of Wisdom), the first scientific and intellectual movement that the city of Baghdad witnessed, as it attracted scholars from Arab and Islamic cities and cities. In the libraries of European countries and the philosophies of their scholars, and the extent of the interest of the Abbasid caliphs and their eagerness to translate it into Arabic, in order to benefit from it in (Bait Al-Hikma) to attract scholars and translators of different nationalities and religions to work with intellectual freedom in (Bait Al-Hikma) without pressure or coercion in their work. Wisdom is an eternal beacon for the various sciences that are being researched. The organized administrative work in the departments and facilities of (Bait Al-Hikma), and the keenness of its employees and their sincerity in their work, had a clear impact on making (Bait Al-Hikma) one of the platforms of science frequented by scholars and their students in order to spread science and reach scientific facts during the medieval era.